How Brand Ambassadors Shape Consumer Purchase Intention: A Study of Local Skincare Brands in Indonesia - Fanni Rizky Adharani; Fatchur Rochman (Journal of Economics Education and Entrepreneurship, 2026)
The increasingly fierce competition in the skincare industry has encouraged companies to utilize brand ambassadors as a marketing strategy to increase consumer purchase intention. However, the effectiveness of brand ambassadors in influencing purchase intention still shows mixed results, particularly regarding the role of brand awareness and brand trust. This study aims to analyze the influence of Brand Ambassadors on Purchase Intention through Brand Awareness and Brand Trust among Whitelab skincare product consumers in Malang City. The study involved 160 prospective Whitelab consumers in Malang City. The findings showed that Brand Ambassador had a positive and significant effect on Purchase Intention, Brand Awareness, and Brand Trust. Brand Awareness did not significantly affect Purchase Intention and did not mediate the relationship between Brand Ambassador and Purchase Intention. In contrast, Brand Trust had a positive and significant effect on Purchase Intention and partially mediated the relationship between Brand Ambassador and Purchase Intention.